2022
DOI: 10.1002/ana.26319
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Excitability Does Not Differ between Painful and Painless Diabetic or Chemotherapy‐Induced Distal Symmetrical Polyneuropathy in a Multicenter Observational Study

Abstract: Objective: Axonal excitability reflects ion channel function, and it is proposed that this may be a biomarker in painful (vs painless) polyneuropathy. Our objective was to investigate the relationship between axonal excitability parameters and chronic neuropathic pain in deeply phenotyped cohorts with diabetic or chemotherapy-induced distal symmetrical polyneuropathy. Methods: Two hundred thirty-nine participants with diabetic polyneuropathy were recruited from sites in the UK and Denmark, and 39 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…Recently, a large multicentre study reported no difference in axonal excitability when comparing those with painless to those with painful diabetic peripheral neuropathy, concluding that electrophysiological measures targeting the small nerves are needed to rule out axonal excitability changes in painful diabetic peripheral neuropathy [42]. One such method is microneurography, which is capable of assessing the function of small cutaneous C-fibres, and have previously associated increased spontaneous activity of cutaneous C-fibres with painful diabetic peripheral neuropathy [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a large multicentre study reported no difference in axonal excitability when comparing those with painless to those with painful diabetic peripheral neuropathy, concluding that electrophysiological measures targeting the small nerves are needed to rule out axonal excitability changes in painful diabetic peripheral neuropathy [42]. One such method is microneurography, which is capable of assessing the function of small cutaneous C-fibres, and have previously associated increased spontaneous activity of cutaneous C-fibres with painful diabetic peripheral neuropathy [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, shorter versions of the motor (TRONDOLM) and sensory (TRONDOLS) TROND protocols were introduced for clinical and research settings that the time ensured for the excitability testing experiments might be limited. These shorter protocols were used in a few recent studies ( Bennedsgaard et al, 2020a , Bennedsgaard et al, 2020b , Kristensen et al, 2021 , Themistocleous et al, 2022 ). However, like the traditional TROND protocols, the test–retest reliability of these protocols has never been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…These protocols have been used in a few recent studies ( Bennedsgaard et al, 2020a , Bennedsgaard et al, 2020b , Kristensen et al, 2021 : Themistocleous et al, 2022 ) but their reliability has yet to be assessed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient partners contributed directly to the consensus meeting and to the development of the PAINSTORM protocol and both of these are very similar to those in DOLORisk (Table 1). Based on 119 ) makes way for microneurography 102,122 ; CPM was omitted as our data from the DOLORisk project suggest that an improved CPM protocol, to be applied and validated in the context of neuropathy, is required 52 ; EEG was not included because as yet the technology for undertaking this at scale is not available; and some participants will take part in imaging studies of the brain, the spinal cord, and the peripheral nervous system. Genetic analysis is likely to include technology advances in both sequencing and analysis for much more comprehensive genomic assessment such as whole genome sequencing.…”
Section: Painstormmentioning
confidence: 99%